Asset Management in Volatile Markets - Peter R. Haiss; Bernhard Sammer; Martin Gartner; Otto Loistl; Stephan Zellner; Christine Zinner; Robert C. Merton; Krzysztof Rybinski; Urszula Sowa (SUERF - The European Money and Finance Forum, 2008)
The 27th SUERF Colloquium in Munich in June 2008: New Trends in Asset Management: Exploring the Implications was already topical in the Summer of 2008. The subsequent dramatic events in the Autumn of 2008 made the presentations in Munich even more relevant to investors and bankers that want to understand what happens in their investment universe. In the present SUERF Study, we have collected a sample of outstanding colloquium contributions under the fitting headline: Asset Management in Volatile Markets.
Keywords: E44; F36; G11; G12; G15; G23; G29; N20; 330; derivatives; financial innovation; asset management; finance-growth-nexus; Relative Value Strategy; Pair Trading; Slippage; Implementation Shortfall; Asset Management; Fin4Cast